(untitled) (International Journal of Agricultural Extension and Education, 2025)
The study examined the role of agricultural extension services and looked at how smallholder farmers in the Niger Delta adopted and used Climate-Smart Agricultural (CSA) practices. Determining the sociodemographic qualities of farmers, estimating the degree of CSA adoption, identifying influencing factors, assessing extension service support, assessing the impact of CSA on livelihoods and resilience, and identifying the difficulties extension services face were the specific goals. Structured questionnaire, focus groups, and key informant interviews were used to gather primary data from 360 smallholder farmers in the states of Bayelsa, Delta, and Rivers. Descriptive statistics, correlation, multiple regression, and Propensity Score Matching (PSM) were used to analyse the data. The findings showed that 40.8% of farmers had a secondary education, 67.5% were men, and the majority were in the productive age range of 30 to 59 years. More than 70% of them implemented CSA techniques, such as crop rotation, the use of organic manure, drought-tolerant crops, and integrated pest management. Education, farm size, credit, climate information, training, and access to extension services all had a significant impact on CSA adoption, according to regression analysis (R2 = 0.742, p < 0.01). The results of the correlation showed that the adoption of CSA and the provision of extension services were strongly positively correlated (r = 0.642–0.713). According to PSM results, CSA adopters’ income (ATT = ₦58,770, p < 0.001) and resilience (ATT = 7.44, p < 0.001) were significantly higher than those of non-adopters. Poor infrastructure, a lack of institutional support, and insufficient funding were major obstacles. Stronger extension capacity, policy support, and farmer cooperatives in the Niger Delta are suggested by the study’s conclusion that efficient agricultural extension services increase CSA adoption, boost resilience, and maintain livelihoods.